2012
DOI: 10.1007/s10899-012-9336-7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Jackpots on EGM Gambling Behavior: A Review

Abstract: IntroductionThis paper reviews literature on how jackpots influence EGM gambling behaviour. Most of the available evidence addresses the motivational effect of the mere presence of EGM jackpots on play, as actual wins are relatively rare for individual gamblers. The review identifies a distinction between rational, biased and irrational motivations that attract people to EGM jackpots. The evidence suggests that EGM jackpots should generate additional consumption on EGMs above machines that do not have such lot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Other authors have similarly observed an important association between this form of gambling and problem gambling. 26 McCready et al 8 8 Thus, the present results confirm and extent those findings by providing a clear demonstration of this relationship in a sample with a large number of problem gamblers. We also observed that reporting sports betting, bingo, and casino table games was also associated with higher odds of problem gambling, as has been observed in previous studies.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Other authors have similarly observed an important association between this form of gambling and problem gambling. 26 McCready et al 8 8 Thus, the present results confirm and extent those findings by providing a clear demonstration of this relationship in a sample with a large number of problem gamblers. We also observed that reporting sports betting, bingo, and casino table games was also associated with higher odds of problem gambling, as has been observed in previous studies.…”
Section: Discussionsupporting
confidence: 86%
“…Other authors have similarly observed an important association between this form of gambling and problem gambling. 26 McCready et al 8 observed, among senior gamblers in the Canadian Community Health Survey 1.2, that more frequent gambling in slots/EGMs was associated with any gambling problems, that is, scoring 1 or more on the PGSI; however, they were unable to assess associations involving problem gambling on the PGSI because of the small numbers of problem gamblers defined by a PGSI score of 8 or above in that sample. 8 Thus, the present results confirm and extent those findings by providing a clear demonstration of this relationship in a sample with a large number of problem gamblers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas jackpots in general do intensify gambling across both lower and higher risk gamblers (Rockloff & Hing, 2013;Rockloff et al, 2014), the presence of jackpots also influences gamblers' EGM game-choice preferences. Delfabbro (2008) found that 30 percent of problem gamblers go to particular venues to play linked jackpot machines compared to three percent of non-problem gamblers.…”
Section: Gaming Machine Characteristicsmentioning
confidence: 99%
“…For example, although the outcome of each play on an EGM is randomly determined and the outcome of each spin is independent from the previous spin, players often hold irrational beliefs about their ability to exert influence over the objectively uncontrollable outcomes in games of chance (Turner & Horbay, 2004;Wohl, Santesso, & Harrigan, 2013). For example, some players believe they possess personal luck that can be used to maximize positive outcomes (Wohl & Enzle, 2003;Wohl, Young, & Hart, 2007) or that the odds of winning increase after a string of losses (Goodie, 2015;Goodie & Fortune, 2013;Hahmann, 2016;Langer, 1975;Rockloff & Hing, 2013). Consequently, it is important for there to be responsible gambling tools that educate the player about their odds of success and correct any irrational beliefs they might have about how EGMs work (Wohl, Christie, Matheson, & Anisman, 2010).…”
Section: The Risks Associated With Egm Playmentioning
confidence: 99%